Healthcare workers' knowledge of indicators for a palliative care approach - Jennie Morgan; Ruth Amoore; Sadiya Z. Patel; Katya Evans; Rene Krause (AOSIS, 2024)
Background: Palliative care is an essential element of universal healthcare, yet not all people who need palliative care are able to receive it. One of the barriers to ensuring access for people who require palliative care is the identification of those eligible. Aim: This study evaluated healthcare workers' ability to identify patients who are eligible for palliative care based on their training or experience in palliative care. Setting: The setting for the study comprised the Heideveld Emergency Centre and Heideveld Community Day Centre in the Cape Metro, Cape Town, South Africa. Methods: This study made use of a cross-sectional survey of healthcare workers. Results: Of the 55 participants in this study, most were able to correctly identify patients with cancer and chronic kidney disease as needing palliative care, but less accurate with other organ failure categories, trauma indications, or functional assessment of the patient. Participants who reported previous awareness training reported improved knowledge on the indications for a palliative care approach compared to no prior training. Conclusion: Our cohort was too small to analyse the results statistically. From what was analysed, the ability of healthcare workers to identify a person in need of palliative care could be better; more work is needed on our awareness training and basic training courses to improve this vital step. Contribution: This research highlights the fact that existing training for palliative care needs to be more applicable to the setting and that training of staff with existing courses does make a difference in knowledge.